Delivering Social Telerehabilitation Services - Marzano, Gilberto; Lubkina, Velta; Rizakova, Lorita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Telerehabilitation is an emerging method of delivering rehabilitation services, which uses information and communication technologies to minimize distance and time barriers. Telerehabilitation is often considered a specialization of the wide field of tele-medicine; most of telerehabilitation services fall into three categories: clinical assessment (patient’s functional abilities in his or her environment), diagnosis and clinical therapy. Researches have recently underlined the potential of social media, mobile phones, and the Internet in general for improving mental health, supporting positive outcomes on addiction issues, sexual health, and homelessness.This paper analyses the issues and implications tied to the development of social telerehabilitation services in Latvia, and reports on the first step of National science program VPP INOSOCTEREHI, a new three years multidisciplinary project on social rehabilitation, which is conducted by four Latvian Universities, and focuses on the use of mobile technologies in rehabilitation scope.